Nrf2 deficiency enhances oxidative stress and promotes susceptibility to tinnitus in mice - Huiwen Yang; Yi Xie; Jintao Yu; Mengwen Shi; Yutian Li; Yifan Cai; Qinming Cai; Fang Huang; Zhewei Ye; Hui Wang; Yu Sun (Scientific Reports)
Abstract Tinnitus is a prevalent and distressing medical symptom, and no effective pharmacological treatment currently exists. Despite significant advances, tinnitus remains a scientific enigma. To explore the molecular underpinnings of tinnitus, we developed a noise-induced tinnitus model in mice and utilized metabolomics to identify key differences in metabolic pathways. Our results revealed that oxidative stress-related pathways, including glutathione (GSH) metabolism, were significantly enriched in the auditory cortex of mice exhibiting tinnitus-like behavior. To further explore the role of oxidative stress, we examined the involvement of nuclear factor erythroid 2-related factor 2 (Nrf2) in tinnitus by conducting experiments in Nrf2 knockout (Nrf2-KO) mice. While Nrf2-deficient mice did not develop spontaneous tinnitus or hearing loss, they displayed increased susceptibility to prolonged tinnitus-like behavior after noise exposure. This was accompanied by heightened microglial activation, neuroinflammation, and significant alterations in gut microbiota composition, including greater diversity and dysbiosis. Our findings highlight a novel mechanism underlying tinnitus, emphasizing the role of oxidative stress in the auditory cortex and its connection to noise-induced tinnitus. The deficiency of Nrf2 in mice increases their susceptibility to tinnitus, suggesting that Nrf2 may serve as a promising therapeutic target for preventing noise-induced tinnitus.